Algebraic number theory - Mollin, Richard A. 1947- (CRC Press series on discrete mathematics and its applications, 1999)
"A follow-up to Dr. Mollin's popular Fundamental Number Theory with Applications, Algebraic Number Theory provides a global approach to the subject, carefully leading the reader through algebraic numbers, the arithmetic of number fields, ideal theory, ideal decomposition in extension fields, and reciprocity laws. In each chapter, the author includes a section on a cryptographic application of the ideas presented, effectively demonstrating the pragmatic side of theory." "Algebraic Number Theory provides a comprehensible yet thorough treatment of the material. Written with the prerequisite background provided in appendices so that anyone can work through the book, this one-of-a-kind text brings the subject matter to life with historical background and real-world practicality."--Jacket.